Jumlah Total Bakteri dalam Saluran Pencernaan Ikan Gurami (Osphronemus Gouramy) Dengan Pemberian Beberapa Pakan Komersial Yang Berbeda [Total Of Bacteria In Digestive Organ Of Gurami Fish (Osphronemus Gouramy) By Administering A Different Commercial Feed] - Boedi Setya Rahardja; Gaby Stephani Rohy; Agustono Agustono (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Gurami is a fish with a slow growth because of the efficiency of utilization of nutrients and energy contained in the feed is too slow, so it is not enough energy available for growth. Feed components that contribute to the provision of materials and energy for growth are proteins, carbohydrates, and fats. The ability of fish to use depends on the nutrient feed enzymes in the digestive organ. Enzyme producing bacteria to help digest fish feed with the help of enzymes produced by the bacteria are protease, lipase and amylase. Determination of Total Plate Count (TPC) has a population of principles that determine the amount of bacteria found in the digestive organ of fish, because the bacteria are the main factors that cause decomposition. The purpose of this study is to obtain total bacterial or Total Plate Count (TPC) in the digestive organ of Gurami (Osphronemus gouramy) given different feed. This study was conducted in July-August, 2013, in the Bacteriology Laboratory of Microbiology, Faculty of Veterinary Medicine, Airlangga University Surabaya. This research is a descriptive research method of solving the problem by describing the subject matter into a form that is easy to understand and based on facts. The results showed that the highest number of total bacteria in the stomach of each type of feed. However, if the average value is taken and compared between the feed is P1, P2 and P3 obtained an average highest number of total bacteria on P2 feed, the average number of bacteria in a row in P1, P2, and P3 are 71.8 x 107 ; 64.5 x 107; 2.9 x 107 which also has the highest crude fiber content of nutrients in the form of a percentage on the proximate test is 8.03%. Expected that the results of this study further research on the addition of probiotic bacteria in the gastrointestinal organ which will help of growth of carp.